2000
DOI: 10.1111/1467-9507.00127
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Infant Skills as Predictors of Child‐Caregiver Joint Attention and Language

Abstract: Current research suggests that the extent to which child-caregiver dyads engage in interactions involving episodes of joint or coordinated attention can have a significant impact on early lexical acquisition. In this regard it has been recognized that individual differences in early developing child communication skills, such as capacity to follow gaze and early infant language, may contribute to these child-caregiver interactional patterns, as well as to subsequent language development. To address this expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 15 publications
(51 reference statements)
5
82
1
2
Order By: Relevance
“…They also showed that the number of 'higher level' joint attention initiations performed by toddlers predicted later expressive language. In a subsequent study (Markus, Mundy, Morales, Delgado & Yale, 2000), infant's ability to respond to joint attention behaviors at 1;0 was correlated with expressive vocabulary size at 1;6. A similar study (Morales, Mundy, Delgado, Yale, Messinger, Neal & Schwartz, 2000) found that a composite estimate of the ability to respond to joint attention behaviors (primarily gaze following) between 0;6 and 1;6 was correlated with both expressive and receptive vocabulary at 2;6.…”
Section: Joint Attention Language and Their Interactionmentioning
confidence: 88%
“…They also showed that the number of 'higher level' joint attention initiations performed by toddlers predicted later expressive language. In a subsequent study (Markus, Mundy, Morales, Delgado & Yale, 2000), infant's ability to respond to joint attention behaviors at 1;0 was correlated with expressive vocabulary size at 1;6. A similar study (Morales, Mundy, Delgado, Yale, Messinger, Neal & Schwartz, 2000) found that a composite estimate of the ability to respond to joint attention behaviors (primarily gaze following) between 0;6 and 1;6 was correlated with both expressive and receptive vocabulary at 2;6.…”
Section: Joint Attention Language and Their Interactionmentioning
confidence: 88%
“…As shown in Figure 2, the negative component of the infant event-related potential, a neural correlate indexing attentional processes [39], was enhanced in amplitude (red line) when infants were engaged in a joint attention interaction compared with a nonjoint attention interaction. Given the interplay between joint attention and later cognitive skills [40,41], the results suggest a general learning mechanism that might underlie a range of cognitive developments. To ascertain whether this is the case, such paradigms should be applied to a range of cognitive skills.…”
Section: Interactive Erp Paradigmsmentioning
confidence: 93%
“…The coordination ofsocial and object schemes represents a qualitative change in infants' cognition (Adamson, 1995;Adamson & Chance, 1998;Sugarman, 1978Sugarman, , 1983. Following this developmental achievement, infants begin to show an ability to collaborate with adults in joint attention and in joint action, and they start to establish collaborative picture book viewing and mutual play with objects (Carpenter et al, 1998;Markus, Mundy, Morales, Delgado, & Yale, 2000;Mundy, Kasari, Sigman, & Ruskin, 1995;Ninio & Bruner, 1978).…”
mentioning
confidence: 99%